Anthropometric nutrition outcomes of children under 5 years undergoing cleft palate repair at CoRSU rehabilitation hospital Uganda; trends, patterns and determinants - Mbuga, Joseph; Galiwango, George William; Tungotyo, Martin (International Journal of Contemporary Pediatrics, 2021)
Background: Objective of the study was to assess the prevalence and determinants of postoperative malnutrition and compare the preoperative and postoperative trends and patterns of malnutrition among children under 5 years undergoing cleft palate repair at CoRSU rehabilitation hospital in Uganda. Methods: A cross-sectional analytical study done between March 2018 and March 2019 at CoRSU rehabilitation hospital; a tertiary rehabilitation hospital offering free comprehensive cleft care to patients from Uganda and beyond. We consecutively enrolled 115 non-syndromic children under 5 years who had undergone complete cleft palate repair at CoRSU hospital at least 3 months previously. Children’s anthropometric parameters; weight for age Z score, height for age Z score and weight for height Z score were obtained and compared at initial, preoperative and postoperative visits. Results: The prevalence of wasting was 53.0% versus 12.7% versus 4.4% that of stunting was 44.4% versus 41.7% versus 48.7% that of underweight was 57.4% versus 34.8% versus 15.7% while that of overweight was 0.0% versus 5.2% versus 9.6% at initial, preoperative and postoperative visits respectively. Postoperative stunting was independently associated with age groups 12-23 months (p=0.013) and 24-59 months (p=0.006), residing in Eastern (p=0.021) and Western (p=0.033) regions and being stunted (p=0.000) or wasted (p=0.028) preoperatively. Conclusions: Postoperatively, the prevalence of both wasting and underweight reduced by 10- and 3- fold respectively; prevalence of stunting remained critically high while that of overweight increased nearly 10-fold. Surgery improves the nutrition status of children with cleft palate.